Recognition of Effective Factors on Farmers will to Take Part in Farming Land Consolidation Plan Performance Case: Khoosf Township - mahmood moradei; mahmood falsoleiman; ameneh abtahineia (جغرافیا و توسعه, 2013)
Lack of farming land Consolidation in all of the cities of the country, has made a lot of problems in appropriate use of production factors and achieving agricultural and rural sustainable development. Proper use of production factors for operating  the potential facilities, implementing the law of land consolidation, making the production as cooperative or gathering small and dispersed farms, creating suitable lands for production and collecting the human and monetary capitals of the villagers,  are considered as the main and basic strategies for achieving the agriculture and rural sustained development. Obviously participation of farmers in farming land Consolidation can be the underlying strategic goals. Farming in South-Khorasan  is faced with an increasing number of problems due to its traditional texture and small units of operation. Therefore,  for  increasing the production output, mechanization of  cultivation, Efficient use of water, improving farm management, land Consolidation plan in 72 Hectares in Khoosf Township in  South-Khorasan  has been performed. In this research, while stating the acceptance scale of farmers, will stusy the effective factors on the tendency of formers for accepting  and participitation in performance of farming land Consolidation plan. Presented research is of applied-development type and its method is descriptive-analytic one. The required data were gathered  through  2 questioners (farmers and experts), interview, observation and making question and were analyzed by using  statistical techniques and Excel & Spss softwares. The obtained results of this research show that there is a meaningful relation between independent variables of age, gender, job & educational level of operators and their will to take part in farming land Consolidation plan.